2021
DOI: 10.1007/s00395-021-00861-z
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 phosphorylation by casein kinase 1 is essential for the cardioprotection by ischemic preconditioning

Abstract: Myocardial connexin 43 (Cx43) forms gap junctions and hemichannels, and is also present within subsarcolemmal mitochondria. The protein is phosphorylated by several kinases including mitogen-activated protein kinase (MAPK), protein kinase C (PKC), and casein kinase 1 (CK1). A reduction in Cx43 content abrogates myocardial infarct size reduction by ischemic preconditioning (IPC). The present study characterizes the contribution of Cx43 phosphorylation towards mitochondrial function, hemichannel activity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 82 publications
2
32
0
Order By: Relevance
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexinbased therapeutic. [65][66][67] Overall, we, here, demonstrated that not only reduced levels of pCx43 and Cx43 but also their apparent internalizations and lateralizations may be associated with abnormal ventricular repolarization, which in turn leads to long-QT in the Aged-group under insulin resistance, similar to the MetS-group. In this regard, although the underlying mechanisms of these two syndromes include alterations in electrophysiological properties of cardiomyocytes besides changes in the heart tissues, further studies are needed to clarify the exact mechanism responsible for the existence of these changes under insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexinbased therapeutic. [65][66][67] Overall, we, here, demonstrated that not only reduced levels of pCx43 and Cx43 but also their apparent internalizations and lateralizations may be associated with abnormal ventricular repolarization, which in turn leads to long-QT in the Aged-group under insulin resistance, similar to the MetS-group. In this regard, although the underlying mechanisms of these two syndromes include alterations in electrophysiological properties of cardiomyocytes besides changes in the heart tissues, further studies are needed to clarify the exact mechanism responsible for the existence of these changes under insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexin-based therapeutic. 6567…”
Section: Discussionmentioning
confidence: 99%
“…The other discrepancy between Cx43 expression in the plasma membrane and L-glutamate release through activated astroglial hemichannels suggests the possibility that subchronic 5-HT1AR activation suppresses hemichannel activity. Cx43 has various phosphorylation sites which receive inhibitory and excitatory regulation [ 76 , 77 , 78 ]. Taken together with the hemichannel regulation system associated with phosphorylation, the suppression of ERK phosphorylation induced by the subchronic administration of BP554 suggests that astroglial L-glutamate release through activated hemichannels is probably reduced by the attenuation of hemichannel activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the central role of mitochondrial HSP90 and connexin 43 (Cx43) in IpostC cardioprotection was shown [ 37 ]. Cx43 is the predominant protein forming gap junctions and hemichannels in the ventricular myocardium, thus crucial for intercellular electrical conduction, cardioprotection and cell survival in mammals [ 38 ]. Application of IpostC on rat heart-derived H9c2 cells and neonatal rat cardiomyocytes resulted in increased total and mitochondrial levels of HSP90, the mitochondria-to-sarcolemma ratio of Cx43, increased levels of Bcl-2 and decreased Bax levels in both sarcolemma and mitochondrial fractions [ 37 ].…”
Section: The Role Of Hsps In Cvdsmentioning
confidence: 99%